Interrelationships between corals and fisheries - Bortone, Stephen A. (CRC Press, 2014)
Interrelationships Between Corals and Fisheries is derived from a workshop held by the Gulf of Mexico Fishery Management Council in Tampa, Florida in May 2013, where world authorities came together to discuss the current problems in managing tropical fisheries and offered suggestions for future directions for both researchers and environmental resource managers. This book addresses current and emerging threats as well as challenges and opportunities for managing corals and associated fisheries. It provides an information baseline toward a better understanding of how corals.
Keywords: Coral reefs and islands -- Monitoring.; Coral reef ecology.; Corals -- Habitat.; Coral reef fishes -- Monitoring.; elektronické knihy; electronic books